Dead or dying? Quantifying the point of no return from hydraulic failure in drought-induced tree mortality - Hammond, William M.; Yu, Kailiang; Wilson, Luke A.; Will, Rodney E.; Anderegg, William R. L.; Adams, Henry D. (The New phytologist, 2019)
Determining physiological mechanisms and thresholds for climate-driven tree die-off could help improve global predictions of future terrestrial carbon sinks. We directly tested for the lethal threshold in hydraulic failure – an inability to move water due to drought-induced xylem embolism – in a pine sapling experiment. In a glasshouse experiment, we exposed loblolly pine (Pinus taeda) saplings (n = 83) to drought-induced water stress ranging from mild to lethal. Before rewatering to relieve drought stress, we measured native hydraulic conductivity and foliar color change. We monitored all measured individuals for survival or mortality. We found a lethal threshold at 80% loss of hydraulic conductivity – a point of hydraulic failure beyond which it is more likely trees will die, than survive, and describe mortality risk across all levels of water stress. Foliar color changes lagged behind hydraulic failure – best predicting when trees had been dead for some time, rather than when they were dying. Our direct measurement of native conductivity, while monitoring the same individuals for survival or mortality, quantifies a continuous probability of mortality risk from hydraulic failure. Predicting tree die-off events and understanding the mechanism involved requires knowledge not only of when trees are dead, but when they begin dying – having passed the point of no return.